Methods in Ecosystem Science - Sala, Osvaldo E.; Jackson, Robert B.; Mooney, Harold A.; Howarth, Robert W. (Springer New York, 2000)
Ecology at the ecosystem level has both necessitated and benefited from new methods and technologies as well as those adapted from other disciplines. With the ascendancy of ecosystem science and management, the need has arisen for a comprehensive treatment of techniques used in this rapidly-growing field. Methods in Ecosystem Science answers that need by synthesizing the advantages, disadvantages and tradeoffs associated with the most commonly used techniques in both aquatic and terrestrial research. The book is divided into sections addressing carbon and energy dynamics, nutrient and water dynamics, manipulative ecosystem experiements and tools to synthesize our understanding of ecosystems. Detailed information about various methods will help researchers choose the most appropriate methods for their particular studies. Prominent scientists discuss how tools from a variety of disciplines can be used in ecosystem science at different scales